Evaluation of the implementation of the perioperative checklist in a public hospital in the Federal District - Valentim Santana Pereira, Ana Cláudia (2022)
Introduction: The World Health Organizationlaunched in 2009 the Safe SurgerySavesLivesProgram. Toachievethetenessentialobjectsproposedbythe World Health Organization, it isnecessaryto use the Safe Surgery Checklist. Objective: toassessthedegreeofimplementationoftheperioperative checklist instrument for safe surgery in a Public Hospital in the Federal District.Method: thisisanexploratorystudythatevaluatedtheimplementationofactivitiesrelatedtotheapplicationofthe checklist in theperioperativeperiod, basedon a qualitative approach.Results: 31 nursingprofessionalswhowork in theSurgical Center participated in thisstudy. Fromtheevaluationmatrix, the checklist itemswerescored in theSing In, Time Out andSing Out times and for eachcheck item a score of 10 points wasestablished, totaling 250 points (100%). The score obtainedafteranalyzingthequestionnaireswas 215 points (86%). Conclusion: the safe surgerysafety checklist performedatthe Hospital Materno-Infantil de Brasília isconsideredimplemented. The complete andcorrectfilling out ofthe checklist instrumentisthebestwaytoachieve real safety for thesurgicalpatient.